The Natural Environment and Landscape As a Tool of Development for and Less Developed Areas: the Attitudes of the Municipality of Vegoritis About the Effects of the Rural Development Policy in the Area - Helen Papadopoulou; Afroditi Efthimiadou; G. Siardos (European Regional Science Association (ERSA), 2006)
A large number of areas in our country are characterized as mountainous and less developed due to some special characteristics of their natural environment and landscape, due to which agriculture operates under serious comparative disadvantages. However, at the same time, these special characteristics of he natural environment and landscape of the remote and mountainous areas can be considered as advantages for other income generating activities, such as alterative types of tourism. More specifically, hills, mountains and lakes, can attract visitors in the area and support leisure fun and sports activities like trekking, climbing, fishing, animal watching and outdoor sports, which can positevely contribute development for the local communities.Both visitors and people of the local communities can be benefited. Visitors relax in a peaceful natural environment whereas the residents of the area can diversify their activities in order to increase their income from other community-based sources. European Community Agricultural and Regional Policy emphasizes the role of the natural environment and landscape of mountainous areas in the community development. Special provision on the Agricultural Development Policy of CAP incorporates the environment in the local development strategy . Local Development Agencies apply a number of Local Development Plans(LDPs) and EU Initiatives, such as Leader in the EU regions with an emphasis on landscape and natural environment management, since 1988. This study examines the role of the LDPs in income generating, employment increase, infrastructure maintenance and improvement and the environment quality and preservation. The attitudes of permanent reseidences of a remote area-of the municipality of Vegoritida-Pella-Greece-towards LDP is also examined. The local stakeholders(residents) were interviewed during November-December 2005, having already a ten years experience of LDPs in their region. Data were processed with SPSS and useful results were drawn about the regional development policy in the agricultural area of Vegoritis.
Keywords: 330